PENERAPAN MODEL PEMBELAJARAN MARKET PLACE ACTIVITY DALAM MENINGKATKAN HASIL PEMBELAJARAN MATERI GERAK BENDA SISWA MI ISLAMIC CENTRE INDRAMAYU - Watiah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This study aims to determine the application of the market place activity learning model in improving learning outcomes of the motion of objects material for students of MI Islamic Center Indramayu. The market place activity learning model was chosen because it can create an active, collaborative, and enjoyable learning atmosphere for students. This study uses a quantitative approach with an experimental method. The subjects of the study were grade III students of MI Islamic Center Indramayu who were divided into two groups, namely the experimental group that applied the market place activity model and the control group that used conventional learning methods. Data were collected through learning outcome tests given before and after the application of the learning model. Data analysis showed that the application of the market place activity model provided a significant increase in learning outcomes of the motion of objects compared to the control group. Students who used the market place activity model showed a better understanding of the concept of motion of objects and were able to apply the material learned more effectively. Based on the results of this study, it can be concluded that the market place activity learning model can be an effective alternative in improving science learning outcomes at the elementary school level. Therefore, this model is recommended to be applied in the learning process in elementary schools, especially in learning science materials.